The impossible journey - Whelan, Gloria (HarperCollins Publishers, 2003)
In 1934, thirteen-year-old Marya and her younger brother, Georgi, set out alone on a long and arduous journey into Siberia to find their mother after she and their father are exiled for opposing Stalin.